2007
DOI: 10.1063/1.2711754
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dislocations on charge carrier mobility–lifetime product in synthetic single crystal diamond

Abstract: The authors report correlations between variations in charge transport of electrons and holes in synthetic single crystal diamond and the presence of nitrogen impurities and dislocations. The spatial distribution of these defects was imaged using their characteristic luminescence emission and compared with maps of carrier drift length measured by ion beam induced charge imaging. The images indicate a reduction of electron and hole mobility-lifetime product due to nitrogen impurities and dislocations. Very good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…These semi-insulating materials are 'super-depleted' at low bias voltages and so operate with an effective space charge region extending throughout the device thickness. [93]. This material was grown by microwave enhanced chemical vapour deposition (CVD) and is a truly monocrystalline epitaxial diamond layer, typically grown in pieces of 5 · 5 mm 2 and up to 1 mm thick.…”
Section: Ibic Charge Transport Measurements In Wide Bandgap Materialsmentioning
confidence: 99%
“…These semi-insulating materials are 'super-depleted' at low bias voltages and so operate with an effective space charge region extending throughout the device thickness. [93]. This material was grown by microwave enhanced chemical vapour deposition (CVD) and is a truly monocrystalline epitaxial diamond layer, typically grown in pieces of 5 · 5 mm 2 and up to 1 mm thick.…”
Section: Ibic Charge Transport Measurements In Wide Bandgap Materialsmentioning
confidence: 99%
“…The horizontal luminescent lines are the introduced nitrogen rich layers. A cathodoluminescence experiment 34 has shown that these nitrogen rich layers emit a signal with a zero phonon line at 2.15 eV, originating from a neutral nitrogen vacancy complex. 35 Additionally, vertical line structures with enhanced blue band A luminescence are also distinguishable.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, single-crystalline chemical vapor deposition ͑SC-CVD͒ diamond exhibits a high saturation drift velocity, high carrier mobilities, 2,3 and high charge collection efficiency with good spatial homogeneity. 4 The maximum resolution, e.g., in imaging biological materials, that can be achieved in x-ray diffraction is today limited by damage. Ultrashort high-intensity x-ray pulses from sources like x-ray free electron lasers, which currently are under development, are expected to extend this limit significantly.…”
Section: Introductionmentioning
confidence: 99%